Recapitulation of Human Neural Microenvironment Signatures in iPSC-Derived NPC 3D Differentiation - Bastos, Joana Campainhas (2019)
"An emerging research field of interest is the use of ionic liquids (ILs) in pharmaceutical applications. For example, their use as drug delivery vehicles has received increasing attention. Finding biocompatible ILs that can improve the solubility and bioavailability of active pharmaceutical ingredients and therapeutic proteins is of upmost relevance in finding solutions for today’s societal challenges.(...)"